2013
DOI: 10.1155/2013/581409
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of TNF-αInhibitors in Rheumatoid Arthritis

Abstract: Background. TNF-α inhibitors have shown to be effective in reducing disease activity and improving the quality of life. Due to the high costs associated with acquisition of this treatment, this study was undertaken to evaluate the ICER of TNF-α antagonists (etanercept, adalimumab, and infliximab) in improving the quality of life. Methods. The HAQ and SF-36 were administered at phases 1, 2, and 3, in order to assess the improvement in the QOL. Suppression of disease activity was assessed through the DAS-28. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Studies show that both adherent-invasive Escherichia coli and H. parainfluenzae are increased in participants with active IBD and may contribute mechanistically to the inflammatory response. 37 In addition, oral microbes including Haemophilus 38 and Streptococcus subspecies show increased colonization during IBD and may contribute to an inflammatory immune response. 39 In contrast, strict anaerobic metabolism is reflected in the pathways of bacteria, including Ruminococcus and Bifidobacterium , associated with health, such as the production of short-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that both adherent-invasive Escherichia coli and H. parainfluenzae are increased in participants with active IBD and may contribute mechanistically to the inflammatory response. 37 In addition, oral microbes including Haemophilus 38 and Streptococcus subspecies show increased colonization during IBD and may contribute to an inflammatory immune response. 39 In contrast, strict anaerobic metabolism is reflected in the pathways of bacteria, including Ruminococcus and Bifidobacterium , associated with health, such as the production of short-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients with JIA who have not responded to conventional DMARDs such as MTX, and who subsequently benefit from treatment with TNF inhibitors, are likely to have improvements in quality of life [35, 4345]. Although TNF inhibitors are more expensive than steroids or synthetic DMARDs, clear benefits are gained in quality of life, increases in productivity, and reductions in healthcare utilization, at least in the adult population [4648]. Formal cost-effectiveness assessments of TNF inhibitors in pediatric JIA patients have shown that switching inadequate responders or non-responders from MTX treatment is associated with better short-term outcomes but at a relatively high cost per quality-adjusted life year (QALY) [35, 4345].…”
Section: Discussionmentioning
confidence: 99%
“…TNF inhibitors are expensive as well as increases the burden of RA patient but Said Cynthia in his research, has revealed that in the short term of 6 months, the patient's quality of life increases and so, the pharmacoeconomic impact also increases eventually 56 . Prior to start with TNF inhibitors, therapy patient should be screened for latent tuberculosis and other preexisting infections.…”
Section: Biologicmentioning
confidence: 99%